All carbohydrate-based nanocomposites composed of sorbitol polyglycidyl ether, aminated trehalose and cellulose nanofiber. (15th March 2020) - Sugai, Koki; Sugane, Kaito; Teramoto, Naozumi; Shibata, Mitsuhiro
Highlights: A sorbitol-based epoxy resin was cured with aminated trehaloses. As a reinforcing fiber of the epoxy-curing system, cellulose nanofiber (CNF) was used. T d5% s of the all carbohydrate-based nanocomposites were higher than 270 °C. When 10 phr of CNF was added, an increase of α-dispersion temperature was observed. The tensile properties were much improved by the addition of CNF. Abstract: Renewable resources-derived nanocomposites are receiving extensive attention because of increasing environmental concern and restricted availability of petrochemical resources. The thiol-ene reaction of cysteamine hydrochloride and allyl-etherified trehaloses (A x Ts) with allyl functionalities of x  = 6 and 8 produced aminated trehaloses (N x Ts). Sorbitol polyglycidyl ether (SPE) was cured with N x Ts in the presence or absence of cellulose nanofibers (CNFs) to give all carbohydrate-based nanocomposites (SPE-N x T/CNFs) or cured resins (SPE-N x Ts). The α-dispersion temperature ( T α ) of SPE-N6T was higher than that of SPE-N8T. The T α for SPE-N6T/CNFs was lowered with increasing CNF content over the range of 0–5 phr, and shifted from lowering to rising at 10 phr. The T α for SPE-N8T/CNFs was not lowered with increasing CNF content, and SPE-N8T/CNF 10 phr exhibited the highest T α among SPE-N8T/CNFs 0–10 phr. The tensile strength and modulus of SPE-N6T/CNF 10 phr were the highest among all the samples, which were much higher than those of SPE-N6T.